2009
DOI: 10.1016/j.ecss.2009.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on the recruitment variability of nursery species

Abstract: a b s t r a c tThe recruitment variability of the marine fish species Dicentrarchus labrax, Platichthys flesus and Solea solea was evaluated in the Mondego estuary (Portugal) from 2003 to 2007. The relationships between sea surface temperature, NAO index, coastal wind speed and direction, precipitation and river runoff prior to the estuarine colonization and the abundance of 0-group fish were evaluated using gamma-based Generalized Linear Models. Dicentrarchus labrax and P. flesus 0-group decreased in abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 58 publications
(77 reference statements)
0
39
0
2
Order By: Relevance
“…We were unable to assess the relationship between plasticity of life history patterns and the area of the river basin and estuary, continental platform width or river discharge. These factors are among the main factors influencing the structure of estuarine fish assemblages (Nicolas et al 2010) and flounder juvenile recruitment (Martinho et al 2009). The inter-annual variability of river discharge may be an indirect driver of flounder life history plasticity, probably due to its control in setting estuarine productivity (Whitfield 1994, Loneragan & Bunn 1999 and in influencing the rate of direct and indirect recruitment of fishes in estuaries (Chícharo et al 2001).…”
Section: Ecological Significance Of Flounder's Diversified Life Histomentioning
confidence: 99%
“…We were unable to assess the relationship between plasticity of life history patterns and the area of the river basin and estuary, continental platform width or river discharge. These factors are among the main factors influencing the structure of estuarine fish assemblages (Nicolas et al 2010) and flounder juvenile recruitment (Martinho et al 2009). The inter-annual variability of river discharge may be an indirect driver of flounder life history plasticity, probably due to its control in setting estuarine productivity (Whitfield 1994, Loneragan & Bunn 1999 and in influencing the rate of direct and indirect recruitment of fishes in estuaries (Chícharo et al 2001).…”
Section: Ecological Significance Of Flounder's Diversified Life Histomentioning
confidence: 99%
“…This temporal variability could be attributed to geographical differences in the environmental factors (water temperature, hydrodinamics, etc.) that regulate fish reproduction and inward migration periods of larvae and juvenile individuals (Martinho et al 2009). …”
Section: Sandy Habitatmentioning
confidence: 99%
“…Costa et al, 2007;Gillson et al, 2009;Martinho et al, 2009), with consequent repercussion on the production levels , as observed by the increased production of Pomatoschistus microps in the years with higher precipitation levels. In general, higher river flow is responsible for an increased transport of organic matter towards estuaries, inducing an increase in primary and secondary production that provides higher food availability for fishes (Costa et al, 2007;Baptista et al, 2010;Dolbeth et al, 2010).…”
Section: Abundance Growth and Productionmentioning
confidence: 99%
“…These impacts can be induced by the alterations in local climate patterns such as temperature, freshwater flow, wind, tidal circulation and currents (e.g. Henderson and Seaby, 2005;Martinho et al, 2009), or by changes in large-scale factors such as North Atlantic Oscillation (NAO) and sea surface temperature (SST) (Attrill and Power, 2002;Vinagre et al, 2009). In addition, local stochastic events such as weather extremes (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation